PERAN FINTECH (FINANCIAL TECHNOLOGY) DALAM MENINGKATKAN DAYA SAING PRODUK DI UKM INDUSTRI ALAS KAKI CIBADUYUT KOTA BANDUNG - Yuniarti, Yuyun; Dinihayati, Erti (Universitas Ahmad Dahlan, 2019)
Footwear business activities in Cibaduyut, Bandung City are supported by various factors, such as entrepreneurial spirit, facilities, marketing, raw material procurement and capital procurement. This research is a qualitative research with data analysis through triangulation. The purpose of this study is mainly to find out the role of Fintech as one of the financial institutions that support in the field of business capital, especially micro-businesses such as Cibaduyut footwear, one of SME in Bandung City. The results of the study show that the Cibaduyut footwear industry is greatly helped by the existence of this Fintech although in the implementation still faces several obstacles, especially those concerning the knowledge and facilities to support these activities.